1976
DOI: 10.1007/bf00583642
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of vascular resistance in two models of experimental renovascular hypertension

Abstract: The regional distribution of the peripheral vascular resistance was studied in normotensive and hypertensive Wistar rats. Two models of experimental hypertension were investigated: (I) in 32 animals the right renal artery was constricted by a silver clip (two-kidney Goldblatt hypertension); (II) in 46 animals the left kidney was removed and the right renal artery was clipped as in the first group (one-kidney Goldblatt hypertension). The normotensive control group comprised 61 untreated animals of the same stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
4
12
1
Order By: Relevance
“…PAGE, 1965;LEDINGHAM and PELLING, 1967;FERRARIO and PAGE, 1974;TERANISHI and IRIUCHIJIMA, 1983). Elevation of vascular resistance is not uniformly distributed over the whole body, but it is especially marked at the superior mesenteric area in two-kidney hypertensive rats (FLOHR et al, 1976;TERANISHI and IRIUCHIJIMA, 1985) and in the renal area in one-kidney hypertenslve rats (TERANISHI and IRIUCHIJIMA, 1988). As shown in Table 3, a similar finding was again observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…PAGE, 1965;LEDINGHAM and PELLING, 1967;FERRARIO and PAGE, 1974;TERANISHI and IRIUCHIJIMA, 1983). Elevation of vascular resistance is not uniformly distributed over the whole body, but it is especially marked at the superior mesenteric area in two-kidney hypertensive rats (FLOHR et al, 1976;TERANISHI and IRIUCHIJIMA, 1985) and in the renal area in one-kidney hypertenslve rats (TERANISHI and IRIUCHIJIMA, 1988). As shown in Table 3, a similar finding was again observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In rats with one-clip, one-kidney renovascular hypertension, by a radioactive particle distribution technique under light ether anesthesia, FLOHR et al (1976) have observed an increase in vascular resistance in skeletal muscle to be higher than that of total peripheral resistance, as we did in SHR. However, such a special involvement of skeletal muscle blood vessels was not observed by BRALET et al (1973) in conscious two-clip renovascular and collodion hypertensive rats by the 86Rb distribution method .…”
Section: Discussionsupporting
confidence: 70%
“…The technique for calibration of the flow meter has been described previously. 18 Mechanical zero flow was checked by momentarily occluding the renal artery in every experiment. The kidney surface was superfused continuously with warm (38° C) isotonic saline from the tip of a quartz rod light conductor.…”
Section: Control Ratsmentioning
confidence: 99%